DEVELOPMENT OF AN ONLINE METAVERSE LESSON USING WITH ACTIVE LEARNING APPROACH TITLED “TECHNOLOGY FOR SOLVING PROBLEMS” IN DESIGN AND TECHNOLOGY COURSE, OF 9TH GRADE STUDENTS - Kasetiam, Nattanon; Roungrong, Passkorn; Raungbandit, Theerachai (Journal of Education and Innovation, 2024)
The purposes of this research were to 1) create and find the effectiveness of an online metaverse lesson using with active learning approach titled Technology for Solving Problems in Design and Technology course of 9th grade students, 2) compare learning outcomes before and after using the online metaverse lesson using with active learning approach titled technology for solving problems in design and technology course of 9th grade students, and 3) study the satisfaction of grade 9 students towards the online metaverse lesson. The sample group used in this research was 40 students from grade 9 of Nakhonsawan school. There were selected by a purposive sampling method. The tools used in the research were; An online metaverse curriculum with active learning, an achievement test, and a satisfaction questionnaire. The research results showed that 1) the online metaverse course was effective according to the criteria set at 87.63/84.97, 2) the sample group had a significantly higher post-test score than the pre-test score at a level of .05, and 3) the students’ satisfaction with the online metaverse course is high ( = 4.46, SD = 0.47).